2013
DOI: 10.4028/www.scientific.net/amm.341-342.511
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis on Protective Airtight Doors of Mine Removable Rescue Capsule

Abstract: In this paper, a cured door structure of mine rescue capsule is proposed, and compared with ordinary flat panel doors. Firstly two kind of three-dimensional solid models of mine removable protective airtight doors are established by the Pro/e software. And then take the advantage of the strength analysis of ANSYS finite element software to draw the stress and strain diagrams. The analysis results show that the strength and stiffness of the curved door is better than ordinary flat panel doors, which provide imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…With the utilization of coal resources, the mining intensity increases year by year, and the underground mining conditions become more complex, resulting in an increase in disasters and accidents, such as fires, explosions, and outbursts. , After a coal mine disaster, the rapid sealing and isolation control of the disaster area can effectively prevent further accidents. , To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. Chang proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the utilization of coal resources, the mining intensity increases year by year, and the underground mining conditions become more complex, resulting in an increase in disasters and accidents, such as fires, explosions, and outbursts. , After a coal mine disaster, the rapid sealing and isolation control of the disaster area can effectively prevent further accidents. , To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. Chang proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 To improve the mine emergency response ability to deal with disasters and accidents, scholars conducted relevant research on the technology and equipment for rapid closed isolation of disaster areas after disasters. 5 7 Chang 8 proposed a solidified door structure for a mine rescue cabin, established a three-dimensional model of a mine mobile protective closed door, and analyzed the strength of an arc door with ANSYS software. The results showed that the strength and stiffness of the arc door are better than those of the ordinary flat door.…”
Section: Introductionmentioning
confidence: 99%